Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 2 . x - 138 = 23 . 32
2 . x - 138 = 72
2 . x = 138 + 72
2 . x = 210
x = 210 : 2
x = 105
\(a,2x-138=2^3\cdot3^2\)
\(2x-138=72\)
\(2x=72+138=210\)
\(x=210:2\)
\(x=105\)
\(b,231-\left(x-6\right)=1339:13\)
\(231-x+6=103\)
\(237-x=103\)
\(x=237-103\)
\(x=134\)
a) 2x - 138 = 23 . 32
=> 2x - 138 = 8 . 9
=> 2x - 138 = 72
=> 2x = 72 + 138
=> 2x = 210
=> x = 210 : 2
=> x = 105
b) 231 - ( x - 6 ) = 1339 : 13
=> 231 - ( x - 6 ) = 103
=> x - 6 = 231 - 103
=> x - 6 = 128
=> x = 128 + 6
=> x = 134
a) 2 . x - 138 = 23.32 b) 231 - (x -6) = 1339 : 13
2. x - 138 = 8 . 9 231 - (x -6 ) = 103
2 . x = 72 + 138 x - 6 = 231 - 103
2. x = 210 x - 6 = 128
x = 210 : 2 x = 128 + 6
x = 105 x = 134
vậy x = 105 vậy x = 134
a) 2.x-138=23.32 b) 231-(x-6)=1339:13
2.x-138=25=32 231-x+6=103
2.x=32+138 231-x=231-103
2.x=160 231-x=128
x=160:2 x=231-128
x=80 x=103
a)
2x - 138 = 23 . 32
=> 2x - 138 = 8 . 9
=> 2x - 138 = 72
=> 2x = 72 + 138
=> 2x = 210
=> x = 210 : 2
=> x = 105
Vậy x = 105
b)
231 - (x - 6) = 1339 : 13
=> 231 - (x - 6) = 103
=> x - 6 = 231 - 103
=> x - 6 = 128
=> x = 128 + 6
=> x = 134
Vậy x = 134
a) 2x-138=23.32
=>2x-138=8.9
=>2x-138=72
=>2x=72+138
=>2x=210
=>x=210:2
=>x=105
b)231-(x-6)=1339:13
=>231-(x-6)=103
=>x-6=231-103
=>x-6=128
=>x=128+6
=>x=134
a) \(\text{2(x-51)=2.2^2+20}\)
\(2\left(x-51\right)=2.4+20\)
\(2\left(x-51\right)=28\)
\(x-51=28\div2\)
\(x-51=14\)
\(x=14+51\)
\(\text{b)3.(x+1)-26=541}\)
\(3.\left(x+1\right)=541+26\)
\(3\cdot\left(x+1\right)=567\)
\(x+1=567\div3\)
\(x+1=189\)
\(x=189-1\)
\(x=188\)
\(x=65\)
\(\text{c)4(x-3)=7^2-1^10}\)
\(4\left(x-3\right)=49-1\)
\(4\left(x-3\right)=48\)
\(x-3=48\div4\)
\(x-3=12\)
\(x=12+3\)
\(x=15\)
\(\text{e)2x-138=2^3.3^2}\)
\(2x-138=8\cdot9\)
\(2x-138=72\)
\(2x=72+138\)
\(2x=210\)
\(x=210\div2\)
\(x=105\)
\(\text{f)(x-1)^4=16}\)
\(\left(x-1\right)^4=2^4\)
\(x-1=2\)
\(x=2+1\)
\(x=3\)
a) (4x - 1)2 = 25.9
=> (4x - 1)2 = 52 . 32 = 152
=> 4x - 1 = 15
=> 4x = 16
=> x = 4
b) 2x + 2x+3 = 144
=> 2x + 2x . 23 = 144
=> 2x (1 + 23) = 144
=> 2x . 9 = 144
=> 2x = 16
=> x = 4
c) đề chắc chắn đúng chứ :v
d) (2x + 1)3 - 12 = 15
=> (2x + 1)3 = 27
=> (2x + 1)3 = 33
=> 2x + 1 = 3 => 2x = 2 => x = 1
2. 2x = 16 => 2x = 24 => x = 4
3x = 81 => 3x = 34 => x = 4
x3 = 64 => x3 = 43 => x = 4
x2 =81 => x2 = 92 => x = 9
\(2^x.\left(2^2\right)^2=\left(2^3\right)^2\)
\(2^x.2^4=2^6\)
\(2^{x+4}=2^6\)
\(\Rightarrow x+4=6\)
\(\Rightarrow x=2\)
<=> 2x.24 = 25
<=> 2x+4 = 25
<=> x+4 = 5
=> x = 5 - 4
=> x = 1
Vaayj x = 1
x=105 nha bạn
x=105 nha bạn